O PROCESSO DE INCLUSÃO SOCIAL DO ALUNO SURDO: ações da ASBRE (Associação dos Surdos de Breves) - SOUSA, Esteliane Santos de (2024)
This work aims to investigate the context of Special Education and the process of inclusion of deaf students in the city of Breves-PA, highlighting the importance of the actions of ASBRE - association of the deaf of Breves, for the integration and social inclusion of your students. The history of special education in its general context, in Brazil and in the municipality of Breves - PA, will be investigated, as well as the laws and decrees dealing with Special Education in Brazil. Finally, we will highlight the process of teaching pounds at ASBRE and the practices developed by the association. The social inclusion of the deaf is a challenge that society faces in times of change, and causes many questions, because for subjects, with and without disabilities, to exercise the full right to citizenship, it is essential that society improves its practices, the in order to meet the individualities. It is also essential to highlight that, as we will see, at the end of this research, how the work of the Association of the Deaf of Breves - ASBRE is essential for the insertion of the deaf in the community / society.